A Sociolinguistic Study of Swear Words Used by Carroll Shelby to His Superiors and Subordinate in Ford v Ferrari. - Michael Jehoshoua Yap; Jusuf Imam Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This study analyzes how Carroll Shelby uses swear words in Ford v Ferrari, focusing on his interactions with his subordinate and his superiors. Using Pinker’s (2007) types of swear words and Holmes’s (2013) sociolinguistic approach, this study aims to identify the types and frequency of swear words, as well as the social factors and dimensions involved in both interactions. A descriptive qualitative method is applied by analyzing selected scenes from the movie. The findings show that Shelby uses three types of swear words, namely idiomatic, emphatic, and abusive, in interactions with both groups. The results further show that the overall frequency of swear words toward subordinates and superiors is not significantly different. Emphatic swearing is the most dominant type in both interactions, while abusive swearing is used more toward the subordinate. Overall, similarities in swearing patterns are more prominent than differences, showing that swearing is shaped by context and pressure.